2021
DOI: 10.1002/ajmg.a.62610
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense variant of SCN4A co‐segregates with congenital essential tremor in a consanguineous Kurdish family

Abstract: Essential tremor (ET) is a neurological disorder characterized by bilateral and symmetric postural, isometric, and kinetic tremors of forelimbs produced during voluntary movements. To date, only a single SCN4A variant has been suggested to cause ET. In continuation of the previous report on the association between SCN4A and ET in a family from Spain, we validated the pathogenicity of a novel SCN4A variant and its involvement in ET in a second family affected by this disease. We recruited a Kurdish family with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…At least in CTC circuits, some of this aberrant electrical activity has been attributed to T-type calcium channels, inhibitors of which are already being developed (Handforth et al, 2010;Scott et al, 2022). Genetic analyses of families with ET have also revealed that mutations in the SCN4A gene, which encodes a voltage-gated sodium channel, segregate with the disease (Bergareche et al, 2015;Asif et al, 2021). Records from mutant SCN4A channels show faster activation and inactivation, which likely contributes to oscillation firing.…”
Section: Disease-based Examplesmentioning
confidence: 99%
“…At least in CTC circuits, some of this aberrant electrical activity has been attributed to T-type calcium channels, inhibitors of which are already being developed (Handforth et al, 2010;Scott et al, 2022). Genetic analyses of families with ET have also revealed that mutations in the SCN4A gene, which encodes a voltage-gated sodium channel, segregate with the disease (Bergareche et al, 2015;Asif et al, 2021). Records from mutant SCN4A channels show faster activation and inactivation, which likely contributes to oscillation firing.…”
Section: Disease-based Examplesmentioning
confidence: 99%